Effect of separated over-fire air on combustion performance of a 3 MW pilot-scale facility. (5th September 2016) - Chen, Kai; Zhang, Jianwen; Che, Defu
Highlights: Numerically and experimentally analyzed a 3 MW pilot-scale facility. The thermal balance formula for the furnace was proposed. The loss of the fuel combustion heat reaches to 8% of the total. The unburnt carbon in the bottom ash leads to the loss of the fuel combustion heat. The position that air injected into furnace affects the sensible enthalpy of air. Abstract: In order to provide references for designing boilers with separated over-fire air (SOFA), numerical simulation was applied for studying the effect of SOFA on temperature, heat flux and fuel combustion in a 3 MW pilot-scale facility. Simulation results agrees well with measureable data. Results show the temperature and the sensible heat flux of the flue-gas at the furnace outlet first decrease, and then increase with the excess air ratio in the combustion zone. As the SOFA ports rises, the temperature and the sensible heat flux of flue-gas decrease at the furnace outlet. These variations are caused by variations of the sensible heat flux of air injected into furnace. Moreover, as the SOFA ratio increases, both the total heat flux from furnace walls and the fuel combustion heat decrease. The maximum decrease of the heat flux from furnace walls occupies 10% of the total in the case without SOFA. The maximum decrease of the fuel combustion heat occupies 8% of the total, which is caused by the unburnt carbon in bottom ash. The SOFA position has little influence on the total heat flux and the fuel combustion heat. These results are valuable for designing boilers with SOFA.